Praktik Wakaf Produktif Kelapa Sawit untuk Pembangunan Musholla Al-Hidayah Perspektif Hukum Islam di Desa Pandan Lagan - Nurul Lailil Munawarah; Nilfatri Nilfatri; Kuswanto Kuswanto; Alisya Pitri; Kurniawan Kurniawan; Haeran Haeran (Journal of Innovative and Creativity, 2025)
Waqf is one of the philanthropic instruments in Islam that holds great potential in supporting social and religious development. This study discusses the practice of productive waqf in the form of an oil palm plantation, where the proceeds are utilized for the construction of the Al-Hidayah prayer room. The purpose of this research is to examine this practice from the perspective of Islamic law and to analyze its implementation within the social context of the community. This study employs an empirical sociological approach by collecting data through field observations and interviews with waqf administrators (nadzir), religious leaders, and local community members. The findings reveal that the productive waqf of oil palm, when managed with trustworthiness and transparency, is considered valid under Islamic law and receives positive support from the community. However, in practice, the negligence of a waqif (donor) who reclaimed the palm trees before the construction was completed constitutes a breach of contract and violates Islamic legal principles. Beyond its role as a form of worship, this practice also offers a practical solution for sustainably funding the construction of worship facilities. The study recommends strengthening regulations and providing guidance to productive waqf managers so that the benefits can be more widespread and well-targeted.